Praca socjalna - eklektyczna czy praktyczna? Rozważania wokół sposobów kształcenia pracowników socjalnych i ich konsekwencji = Social work - eclectic or practical? Reflections on the ways of training social workers and their consequences - Bury, Przemysław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Alongside revolution, political transformation is one of the fundamental forms of transforming reality and creating a new political, economical and social order. The Polish transformation of the 1990s meant a move away from the system of popular democracy, which implemented the "great ideas of socialism" towards parliamentary democracy and the constitutional principle of a "social market economy". This radical process bene?ted the vast majority of the Polish society in many ways, but there are still groups that are unable to cope with the new reality.
Keywords: pomoc społeczna; pracownik socjalny; kształcenie; social assistance; social worker; training